Towards inclusive governance for resilient agri-food systems in Bangladesh - Irfanullah, Haseeb; Asaduzzaman, Mohammed; Joshi, Deepa; Aheeyar, Mohamed M. M.; Dikkumbura, Sahani; Rahman, M. Mokhlesur; Islam, M. Anisul (International Water Management Institute, 2023)
This policy brief — produced under the CGIAR Initiative on Asian Mega-Deltas (AMD) — emphasizes the urgent need for promoting inclusive governance in Bangladesh's agri-food systems to enhance resilience in the face of escalating climate risks. Although Bangladesh is transitioning toward climate-resilient agri-food systems, this shift faces challenges. There is notable variation among policies and interventions pertaining to food, water and environmental systems in their acknowledgment of socio-ecological interdependencies and representation of marginalized communities. This highlights the need for policies that address interlinked social, economic and political inequalities within the agri-food sector and translating the policies into practice. A gap also exists between local experiences of food insecurity and climate resilience and expert-led innovations. Key recommendations in this brief call for the promotion of nature-based solutions, leveraging the progressive National Adaptation Plan, and establishing a robust gender-focused fiscal system. These recommendations, which are aligned with the eight principles of locally led adaptation, underscore the vital role of empowering local communities to lead effective climate change adaptation efforts, ultimately fostering a more sustainable and resilient agri-food sector in Bangladesh.